Generation of trophoblast-like cells from the amnion in vitro: A novel cellular model for trophoblast development - Wei, Yanxing; Zhou, Xiaohua; Huang, Wenhao; Long, Ping; Xiao, Lu; Zhang, Tian; Zhong, Mei; Pan, Guangjin; Ma, Yanlin; Yu, Yanhong (Placenta (Eastbourne), 2017)
Despite the high incidence of trophoblast-related diseases, the molecular mechanism of inadequate early trophoblast development is still unclear due to the lack of an appropriate cellular model in vitro. In the present study, we reprogrammed the amniotic cells to be induced pluripotent stem cells (iPSCs) via a non-virus and non-integrated method and subsequently differentiated them into trophoblast-like cells by a modified BMP4 strategy in E6 medium. Compared with the previously studied trophoblast-like cells from ESCs, the iPSCs derived trophoblast-like cells behave similarly in terms of gene expression profiles and biofunctions. Also we confirmed the differentiating tendency from iPSCs to be syncytiotrophoblasts-like cells might be caused by inappropriate differentiating oxygen condition. Additionally, we preliminarily indicated in vitro “artificial” differentiation of iPSCs also undergoing a possible trophoblastic stem cell stage, as witnessed in vivo. In conclusion, we provided an in vitro cellular model to study early trophoblast development for specific individual, by using the feasible amnion. •Amniotic cells were successfully reprogrammed with non-virus and non-integrated method.•The iPS cells could be differentiated to be trophoblast-like cells similar to ESCs via a possible transient trophoblastic stem cell stage.